2011
DOI: 10.1104/pp.111.186288
|View full text |Cite
|
Sign up to set email alerts
|

Missense Mutation in the Amino Terminus of Phytochrome A Disrupts the Nuclear Import of the Photoreceptor    

Abstract: Phytochromes are the red/far-red photoreceptors in higher plants. Among them, phytochrome A (PHYA) is responsible for the far-red high-irradiance response and for the perception of very low amounts of light, initiating the very-low-fluence response. Here, we report a detailed physiological and molecular characterization of the phyA-5 mutant of Arabidopsis (Arabidopsis thaliana), which displays hyposensitivity to continuous low-intensity far-red light and shows reduced very-low-fluence response and high-irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 71 publications
2
9
0
Order By: Relevance
“…Six-day-old dark-grown seedlings were then subjected to various light treatments, as described in the text. The standard epifluorescence microscopy set-up and observation techniques have been described previously (Bauer et al, 2004;Viczi an & Kircher, 2010;Sokolova et al, 2012). For semiquantitative epifluorescence microscopy, etiolated seedlings were irradiated for 6 h with R light at the fluence rates given in the figure legends.…”
Section: Epifluorescence Microscopymentioning
confidence: 99%
“…Six-day-old dark-grown seedlings were then subjected to various light treatments, as described in the text. The standard epifluorescence microscopy set-up and observation techniques have been described previously (Bauer et al, 2004;Viczi an & Kircher, 2010;Sokolova et al, 2012). For semiquantitative epifluorescence microscopy, etiolated seedlings were irradiated for 6 h with R light at the fluence rates given in the figure legends.…”
Section: Epifluorescence Microscopymentioning
confidence: 99%
“…It is well established that the nuclear localization facilitators FHY1 and FHL play a critical role in this process (Hiltbrunner et al, 2005(Hiltbrunner et al, , 2006Rösler et al, 2007;Genoud et al, 2008). The N-terminal fragment of phyA, which binds FHY1 in yeast cells (Hiltbrunner et al, 2005), accumulates in the nucleus under continuous FR (Pfeiffer et al, 2009;Wolf et al, 2011), whereas the missense mutation in the N-terminal extension impairs FR-induced nuclear accumulation (Sokolova et al, 2012). This result is also consistent with the recent model in which the association/dissociation of the phyA-FHY1/FHL complex plays an important role in FR-HIR (Rausenberger et al, 2011).…”
Section: Discussion Intracellular Localization Of Phya/phyb Chimeric mentioning
confidence: 99%
“…9 Very recently, we identified and described a mutant (phyA-5) expressing PHYA with a missense mutation. 10 This mutant line shows a fairly complex phyA-specific phenotype, including a reduced nuclear import at low intensities of FR indicating that the point mutation identified alters the FHY1/FHL-phyA Pfr association/dissociation "cycle." The fact that PHYA-5 governs wild-typelike signaling when it is fused to a nuclear localization signal (NLS), strongly supported this conclusion.…”
mentioning
confidence: 93%
“…The fact that PHYA-5 governs wild-typelike signaling when it is fused to a nuclear localization signal (NLS), strongly supported this conclusion. 10 Our knowledge about the interaction of phyA with the FHY1 and FHL proteins is rather limited. Yeast two-hybrid assays showed that the Pfr form of the phyA406 (1-406 amino acids) specifically binds the FHY1/FHL transporter molecules.…”
mentioning
confidence: 99%